Connecting hillslope and runoff generation processes in the Ethiopian highlands: the Ene-Chilala Watershed - Addisie, M.B.; Ayele, G.K.; Hailu, N.; Langendoen, E.J.; Tilahun, Seifu A.; Schmitter, Petra S.; Parlange, J.Y.; Steenhuis, Tammo S. (Walter de Gruyter GmbH, 2020)
Effective watershed planning requires an understanding of the hydrology. In the humid tropical monsoon climates and especially in volcanic highland regions such as the Ethiopian Highlands, the understanding of watershed processes is incomplete. The objective is to better understand the hydrology of the volcanic regions in the humid highlands by linking the hillslope processes with the discharge at the outlet. The Ene-Chilala watershed was selected for this study. The infiltration rate, piezometric water levels and discharge from two nested sub watersheds and at the watershed outlet were measured during a four-year period. Infiltration rates on the hillsides exceeded the rainfall intensity most of the time. The excess rain recharged a perched hillside aquifer. Water flowed through the perched aquifer as interflow to rivers and outlet. In addition, saturation excess overland flow was generated in the valley bottoms. Perched water tables heights were predicted by summing up the recharge over the travel time from the watershed divide. Travel times ranged from a few days for piezometers close to the divide to 40 days near the outlet. River discharge was simulated by adding the interflow from the upland to overland flow from the saturated valley bottom lands. Overland flow accounted only for one-fourth of the total flow. There was good agreement between predicted and observed discharge during the rain phase therefore the hillslope hydrologically processes were successfully linked with the discharge at the outlet.